Daughter of dusk - Blackburne, Livia (Hyperion, 2015)
"As tensions rise within Forge's Council, and vicious Demon Rider attacks continue in surrounding villages, Kyra knows she must do something to save her city. But she walks a dangerous line between opposing armies: will she be able to use her link to the Demon Riders for good, or will her Makvani blood prove to be deadly? Kyra and Tristam face their biggest battle yet as they grapple with changing allegiances, shocking deceit, and vengeful opponents"--